Identification of complement activation sites in human immunodeficiency virus type-1 glycoprotein gp120 - Süsal, Caner; Kirschfink, Michael; Kröpelin, Marianne; Daniel, Volker; Opelz, Gerhard (Blood, 1996)
Recombinant glycoprotein 120 (rgp120) of human immunodeficiency virus type-1 (HIV-1) activates the human complement system in the absence of anti-gp120 antibodies. HIV-1 glycoprotein gp120 can dissociate from the viral envelope either spontaneously or after binding of HIV-1 to the CD4 molecule. As a consequence, gp120 can circulate in the patient's serum and attach to the surface of uninfected CD4+ T cells. Complement activation by cell-bound HIV-1 glycoprotein gp120 with subsequent opsonization may represent a mechanism for the elimination of uninfected CD4+ cells by the reticuloendothelial system, thereby enhancing the progression of HIV disease. In the current study, the complement proteins C4, C3, C5, C9, and properdin were found to bind to a synthetic peptide covering positions 233-251 of the gp120BRU sequence on incubation with normal human serum. Complement activation by the peptide was comparable with that induced by aggregated IgG, complete rgp120, and the previously described complement-activating gp41-peptide 609-623. Activation occurred via the classical pathway and was abrogated in the presence of EDTA, Mg2+/EGTA, or C4-deficient human serum. Peptides partly overlapping the sequence 233-251 activated complement to a lesser extent. The complement-activating capacity of the gp120 sequence 233-251 was not restricted to the HIV-1BRU isolate, because a peptide from the corresponding sequence of the HIV-1MN strain was also capable of activating complement. An additional strong complement-activating site was identified in the gp120 sequence 321-360 of the HIV-1MN strain. These data indicate that distinct sites in gp120 are able to activate human serum complement via the classical pathway in the absence of anti-gp120 and independent of glyco-sylation.
Elektronische Reproduktion der Druck-Ausgabe 14. Dezember 2020
Gesehen am 15.08.2024